Comparative physiological and transcriptomic analyses provide induction resistance mechanisms of Bacillus tequilensis against Colletotrichum fructicola in Camellia oleifera - Zhou, Aiting (Plant physiology and biochemistry : PPB, 2024)
Copyright © 2024 Elsevier Masson SAS. All rights reserved.